Turkish foreign aid to Northern Cyprus: a mother's blessing or curse?. Issue 3 (3rd July 2021) - Ekici, Tufan; Özdemir, Yonca
ABSTRACT: This paper talks about the impact of Turkish aid on the macroeconomic development of Northern Cyprus. Since the physical division of the island of Cyprus in 1974, Turkey has been sending considerable financial aid to the de-facto state in its northern part, but the impact of this aid on local economics and politics has been controversial. We show that foreign aid has not been directly relevant for economic growth of Northern Cyprus. We suggest that persistence of aid, despite its negative impacts, can be explained by Turkey's geopolitical interests on the island.